KOMPETENSI LITERASI SAINS SISWA SE-KECAMATAN KEDATON PADA KONTEN BIOLOGI - Rizki Samty; Tri Jalmo; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2016)
The purpose of this research was to find out the competence of scientific lieracy of student. The research design was using simple descriptive design, by using purposive sampling technique, as many as 197 students. The quantitative data were scientific literacy competence that was obtained from PISA test and the qualitative data were factors influenced that were obtained from questionnaire.  The result of the research shows that the students’ had very low category with the score 19,6 ± 3,0. The score of female students was 26,0 1,79 significantly different with male student that was 21,2  1,18 and showed the difference but it very not significant. The factors that influence students’ were parents’ education background, home work of students, the learning process including the length of studying science at school, participation in attending lesson and teacher who teaches the course. Thus, scientific literacy competence was “very poor” criteria and there were factors that affected that. Then significantly differences between male and female students competence. Penelitian ini bertujuan untuk mengetahui profil kompetensi literasi sains siswa. Desain penelitian yaitu studi deskriptif, dengan teknik  purposive sampling berjumlah 197 siswa. Data kuantitatif berupa skor kompetensi literasi sains dengan soal  PISA dan data kualitatif berupa faktor yang mempengaruhi dengan menggunakan kuisioner. Dianalisis secara deskriptif. Hasil penelitian kompetensi  literasi sains siswa kriteria “sangat rendah” (19,6 ± 3,0). Aspek yang tertinggi yaitu “menggunakan bukti ilmiah”. Kompetensi literasi sains siswa perempuan (26,0 1,79) berbeda tidak signifikan dengan siswa laki-laki (21,2  1,18). Faktor yang berpengaruh yaitu latar belakang pendidikan orang tua; pemberian PR; proses pembelajaran meliputi lama belajar sains di sekolah, keikutsertaan les dan guru yang mengajar les. Dengan demikian, disimpulkan bahwa kompetensi literasi sains tergolong “sangat rendah” dan terdapat faktor-faktor yang mempengaruhinya. Perbedaan yang tidak signifikan antara kompetensi laki-laki dan perempuan. Kata Kunci:  faktor, gender, literasi sains, PISA